PENGARUH PENDIDIKAN ETIKA TERHADAP PERSEPSI ETIS MAHASISWA AKUNTANSI - Sari, Padma Adriana (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2018)
The Influence of Business Ethics Education to Ethical Perception of Accounting StudentsThe main focus of this study is to understand the effect of business ethic course to student’s ethical perception. This study used survey method in gathering the data, which used students from Politeknik Negeri Malang as the participants. Ethical perception was assessed by giving scenarios abaout unethical accountants, and students were asked to respond to questions about the scenarios. The analysis data method used independent sample t-test. The result of this study indicates that there were no significant difference between student’s perceptions who have accomplished business ethics course and who have not accomplished the course yet.Keywords: Ethics Education, Ethical Perception.